SUCCESSFUL THROMBOEMBOLECTOMY THROUGH THE RIGHT INTERNAL CAROTID ARTERY LUMEN WITH STENT-RETRIEVER APPLICATION AND FURTHER BALLOON ANGIOPLASTY - A. I. Beliy; V. V. Efimov; O. S. Volkolup; R. A. Tupikin (Инновационная медицина Кубани)
For the last several years while treating acute ischemic strokes methods of endovascular interventions are favorably applied. Similar treatment methods are characterized by large therapeutic window, high efficiency and effect persistence comparing to systemic thrombolytic therapy. In the present article we present clinic observance for endovascular mechanical thromboembolectomy with stent-retriever and further balloon angioplasty in a patient with acute ischemic stroke in the area of stenotic lesion of internal carotid artery wedge-shaped aspect.